The resulting point by considering that P(x, y) = (6, - 1) and P'(x, y) = P(x, y) + (- 5, - 2) is equal to the coordinates P'(x, y) = (1, - 3). (Right choice: C)
In this question we need to determine the new location of a point by using a translation formula. Translations are rigid transformations in which a point is translated on a Cartesian plane. We have the following formula:
P'(x, y) = P(x, y) + (- 5, - 2) (1)
Where:
If we know that P(x, y) = (6, - 1), then the resulting point is:
P'(x, y) = (6, - 1) + (- 5, - 2)
P'(x, y) = (1, - 3)
The resulting point by considering that P(x, y) = (6, - 1) and P'(x, y) = P(x, y) + (- 5, - 2) is equal to the coordinates P'(x, y) = (1, - 3). (Right choice: C)
To learn more on translations: https://brainly.com/question/17152175
#SPJ1